Investigation of the Proliferation of the Vector Aedes aegypti in the Municipality of Abaiara - Ceará from 2014 to 2017 (Revista Brasileira Multidisciplinar, 2026)
Large cities benefit from epidemiological research and vector infestation studies toplan actions against dengue. However, in smaller areas, the lack of comprehensivestudies results in complications when cases increase, affecting both managers andthe population. This work aims to understand the relationship between rainfall,confirmed dengue cases, and infested properties in Abaiara-CE from 2014 to 2017.The methods included documentary, quantitative, and qualitative research, with datacollected through the Rapid Index Survey (LIRAa) and the Laboratory EnvironmentManager (GAL). Rainfall data were obtained from FUNCEME. Correlation testsbetween rainfall indices and Aedes aegypti infestation were conducted using the Rprogram, and graphs were generated in Excel. A positive correlation (0.60) wasobserved between the Property Infestation Index and the accumulated rainfall in eachinspection cycle. A positive correlation (0.55) was also found between confirmeddengue cases and rainfall. This correlation was stronger in 2014, 2015, and 2017. Aweak negative correlation (-0.26) was noted between the duration of the previouscycle and the number of positive properties in the following cycle. The results aresimilar to those found in large cities. Data from endemic agents are essential, andtheir analysis can support actions to combat arboviruses transmitted by A. aegypti,even in small cities.
Keywords: arboviruses; Epidemiology; Climate correlation